Interaksi Debt To Equity Ratio, Current Ratio, Firm Size, Dan Dividend Payout Ratio: Interaction of Debt To Equity Ratio, Current Ratio, Firm Size, And Dividend Payout Ratio - Ariska, Ricky Angga (Journal of Accounting Science, 2018)
This research aims to know the effect of debt to equity ratio, current ratio, and firm size on the dividend payout ratio in State Owned Enterprises (BUMN). Secondary data is used in this research, while the sampling technique in is purposive. Criteria for samples are BUMN that is listed in Indonnesian Stock Exchange (BEI) in 2012-2014, having profit during 2012-2014, and having complete financial report during 2012-2014. There are five enterprises that meet these criteria. The researcher used doubled linear regression for the analysis. The results showed that debt to equity ratio, current ratio, and firm size have simultaneous effect on dividend payout ratio. The results also shows that only current ratio has partial effect on the dividend payout ratio. Meanwhile, debt on equity ratio and firm size have no partial effect on dividend payout ratio.